Telemedicine-Supported Hybrid Primary Care in Rural Areas with Healthcare Workforce Shortages: A Qualitative Study from the Heves District, Hungary - Viktor Rekenyi; János Sándor; Ferenc Nagy; Csongor István Szepesi; Nóra Horváth; Yoram T. Kohut; Dániel Eörsi; Anita Pálinkás; Janka Juhász; Hunor Györpál; László Róbert Kolozsvári (Healthcare, 2026)
Background/Objectives: Primary healthcare in Hungary faces acute physician shortages; in the Heves district, eight general practices are permanently vacant, leaving 11,191 residents without continuous care. In September 2025, the Hungarian Charity Service of the Order of Malta launched the Heves Haziorvosi Pilot (HHP), combining on-site nurse triage with remote telemedicine consultations. This study qualitatively evaluated its implementation and early operation. Methods: Three focus group discussions were held in two rounds, before and after implementation, with all 19 professionals delivering the programme (10 practice nurses, 4 general practitioners, 5 degreed professionals). Verbatim Hungarian transcripts were analysed in NVivo 15 (Lumivero, Denver, CO, USA) using the thematic analysis framework of Braun and Clarke with hybrid deductive-inductive coding by three independent researchers until full consensus. Results: Daily physician availability rose from approximately 2 to 8 h, and one remote physician concurrently supported four practices. Participants reported reduced professional isolation among nurses, longer and more focused consultations, and perceived, though unquantified, decreases in non-urgent ambulance use. Implementation was constrained by duplicate paper and digital documentation, patients’ limited familiarity with triage, and unresolved software interoperability and IT ergonomic problems. Conclusions: The hybrid model was perceived as operationally feasible; national scaling would require nursing curriculum reform, administrative simplification, interoperable medical software, and community health literacy programmes.